Delayed presentation of pulmonary artery perforation by an Amulet left atrial appendage closure device. (3rd November 2018) - Wang, Edward; Lin, Wah Wah; Xu, Xiao Fang; Merry, Chris
Abstract : Left atrial appendage occlusion (LAAO) devices offer stroke prevention in atrial fibrillation for patients intolerant of anticoagulation. Device placement leading to bleeding and cardiac tamponade have been reported periprocedurally but delayed presentations have not been reported in the literature. We present the case of an Amulet LAAO device causing erosion and bleeding from the main pulmonary artery that presented with cardiac tamponade 6 months after device placement. The pulmonary artery defect was repaired primarily and buttressed with a pericardial patch with good result.